Indian art of the pueblos - Phelps, Bill; Van Bork, Bert (The Corp., 1976)
Examines the traditional materials, forms and symbols that characterize the Indian Art of the American Southwest. Describes the religious and significance of these works in the daily lives of the Pueblo people.